Ethics, computing, and medicine : informatics and the transformation of health care - Goodman, Kenneth W., 1954- (Cambridge ; New York, N.Y. : Cambridge University Press, 1998)
New technology always raises compelling ethical questions. As those in medicine increasingly depend on computers and other intelligent machines, the intersection of ethics, computing and the health professions grows much more complex and significant. This book attempts systematically to identify and address the full range of ethical issues that arise when intelligent machines are used in medicine, nursing, psychology, and allied health professions. It maps and explores a variety of important issues and controversies, including ethics and evaluation in computational medicine, patient and provider confidentiality, responsibility for use of computers in medicine, appropriate use of decision support systems, outcomes of research and computational prognosis (including mortality predictions), and computer-based biomedical research - especially meta-analysis. This book is accessible to participants in the fields of bioethics and medical informatics. It is appropriate for physicians, nurses, administrators, ethicists, health attorneys, advanced undergraduates and graduate students.
Bioethics and health informatics : an introduction / Kenneth W. Goodman -- Medical informatics and human values / Terrell Ward Bynum and John L. Fodor -- Responsibility for computer-based decisions in health care / John W. Snapper -- Evaluating medical information systems : social contexts and ethical challenges / James G. Anderson and Carolyn E. Aydin -- Health care information : access, confidentiality, and good practice / Sheri A. Alpert -- Ethical challenges in the use of decision-support software in clinical practice / Randolph A. Miller and Kenneth W. Goodman -- Outcomes, futility, and health policy research / Kenneth W. Goodman -- Meta-analysis : conceptual, ethical, and policy issues / Kenneth W. Goodman.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Medicine -- Data processing -- Moral and ethical aspects; Medical records; Risk; Managed care plans (Medical care); Confidential communications; Economics; Medical care; Probabilities; Social values; Bioethics; Decision making; Evidence-based medicine; Informed consent (Medical law); Physician and patient; Risk assessment; Computer networks; Telecommunication in medicine; Information services; Vocational qualifications; Philosophy; Thought and thinking; Medical personnel and patient; National health services; Social psychology; Health services accessibility; Social control; Medical personnel; Computer systems; Humanities; Forensic psychiatry; Prognosis; Communication; Risk management; Clinical medicine; Health services administration; Social sciences; Statistics; Weights and measures; Telecommunication; Health planning; Therapeutics; Human rights; Social groups; Human information processing; Human behavior; Sociology; Information storage and retrieval systems; Public health; Diagnosis; Mass media; Misinformation; Statistics -- Methodology; Health Care Rationing; Medical Futility; Medical Informatics; Medical Records; Risk; Managed Care Programs; Withholding Treatment; Confidentiality